Meter as rhythm - Hasty, Christopher Francis (Oxford University Press, 1997)
In this book Christopher Hasty presents a striking new theory of musical duration. Drawing on insights from modern "process" philosophy, he advances a fully temporal perspective in which metre is released from its mechanistic connotations and recognized as a concrete, visceral agent of musical expression. Part one of the book reviews oppositions of law and freedom, structure and process, determinacy and indeterminacy in the speculations of theorists from the eighteenth century to the present. Part two reinterprets these contrasts to form a highly original account of metre that engages diverse musical repertories and aesthetic issues.